Rudolf Hess – The Doppelgänger conspiracy theory disproved. (May 2019) - McCall, Sherman; Kreindl, Gabriele; Kastinger, Tamara; Müller, Eva; Zahrer, Waltraud; Grießner, Ines; Dunkelmann, Bettina; Tutsch-Bauer, Edith; Neuhuber, Franz; Pittman, Phillip R.; Wahl, Rick; Lowry, Mark; et al.
Highlights: STR typing on the of the only known extant DNA sample from prisoner 'Spandau #7', believed to be Rudolf Hess, Deputy Führer of the Third Reich. Refutation of the so called "Doppelgänger Conspiracy Theory" by comparison with reference sample from the Hess male line. Valuable amendment of the recent history record of the Third Reich Period. Abstract: The Deputy Führer of the Third Reich Rudolf Hess was captured after a controversial flight to Scotland in 1941. Hess was sentenced to life imprisonment during the Nuremberg War Crimes Trials. He was detained in Berlin's Spandau Prison under the official security designation 'Spandau #7.' Early doubts arose about the true identity of prisoner 'Spandau #7.' This evolved to a frequently espoused conspiracy theory that prisoner 'Spandau #7' was an imposter and not Rudolf Hess. After Hess's reputed 1987 suicide, the family grave became a Neo-Nazi pilgrimage site. In 2011, the grave was abandoned and the family remains cremated. Here we report the forensic DNA analysis of the only known extant DNA sample from prisoner 'Spandau #7' and a match to the Hess male line, thereby refuting the Doppelgänger Theory.